Recognising refugees' nonformally and informally acquired vocational skills for use in Germany's labour market - Windisch, Hendrickje Catriona (Bundesinstitut für Berufsbildung, 2020)
"The influx of asylum seekers into the European Union (EU) in 2015-2016 has turned the recognition of non-formal and informal learning (NFIL) into an integration priority and challenge. In EU terminology this process is called 'validation'. Already in 2012, the Council of the EU had urged member states to create mechanisms for the validation of NFIL by no later than 2018. However, the issue has remained systematically addressed by few. Moreover, across all countries, disadvantaged groups such as refugees still benefit least from validation. Yet little is known about the reasons for this - a question to which this study aims to contribute understanding. Notably Germany has lagged behind many other countries on the issue. Germany was selected as the research site because compared to other European countries, it accepted the largest number of refugees in 2015-2016. Additionally, its highly regulated labour market and well-established dual apprenticeship system makes formal skills recognition particularly relevant for refugees who only possess non-formally and informally acquired vocational skills (NFIVOS) as such recognition would enable these individuals to access skilled jobs that in Germany typically require formal vocational or professional qualifications. The data from this study were analysed using Bourdieu's theory of practice (1977b, 1986) with its concepts of field, capital and habitus. In so doing, it became clear that the biggest infrastructural barrier to the formal recognition of refugees' NFIVOS was Germany's lack of an arrangement that fulfilled this purpose in a refugee-friendly way. This could be seen as the result of Germany's selective inclusion of foreign institutionalised habitus but exclusion of foreign embodied habitus (except when the latter was supplemented by a German institutionalised habitus) in the skills recognition procedures which transform foreign habitus into German institutionalised cultural capital. Given this lack of a refugee-friendly procedure, the study makes inferences from its 14 case studies about what could fill this gap and finds that potential facilitating factors are an interplay of Germany's integration infrastructure and refugees' personal agency. As a consequence, it is argued that refugees' obstacles and facilitators in gaining formal skills recognition are the result of a mismatch and alignment, respectively, of refugees' habitus with the requirements of Germany's skills recognition field." (Authors' abstract ; BIBB-Doku)

"Der Zustrom von Asylbewerbern in die Europäische Union (EU) in den Jahren 2015-2016 hat die Anerkennung des nicht formalen und informellen Lernens (NFIL) zu einer Integrationspriorität und -herausforderung gemacht. In der Terminologie der EU wird dieser Prozess als „Validierung“ bezeichnet. Bereits 2012 hatte der Rat der EU die Mitgliedstaaten aufgefordert, bis spätestens 2018 Mechanismen für die Validierung von NFIL zu schaffen. Das Thema ist seither lediglich von wenigen Ländern systematisch angegangen worden. Darüber hinaus profitieren benachteiligte Gruppen wie Flüchtlinge nach wie vor in allen Ländern am wenigsten von Validierungsmaßnahmen. Über die Gründe hierfür ist jedoch wenig bekannt – eine Fragestellung, zu der diese Studie Antworten beizutragen sucht. Insbesondere Deutschland ist in diesem Themenbereich hinter vielen anderen Ländern zurückgeblieben. Deutschland wurde als Forschungsstandort ausgewählt, da es im Vergleich zu anderen europäischen Ländern in den Jahren 2015-2016 die meisten Flüchtlinge aufgenommen hat. Darüber hinaus machen Deutschlands stark regulierter Arbeitsmarkt und die gut etablierte duale Berufsausbildung die formelle Fähigkeitsanerkennung besonders relevant für Flüchtlinge, die nur über nicht formal und informell erworbene berufliche Fähigkeiten (hier abgekürzt als NFIBEF) verfügen. Solch eine Anerkennung würde ihnen den Zugang zu qualifizierten Arbeitsplätzen ermöglichen, die in der Regel formale Berufsqualifikationen erfordern. Um die erschwerenden und erleichternden Faktoren bei der Anerkennung der NFIBEF von Flüchtlingen für die Verwendung auf dem deutschen Arbeitsmarkt zu untersuchen, wurden in dieser Studie unstrukturierte Interviews mit Flüchtlingen (N = 7) und halbstrukturierte Interviews mit Personen (N = 53) geführt, die zur Fähigkeitsanerkennung und mit Flüchtlingen auf operativer und strategischer Ebene arbeiten. Darüber hinaus wurden Beobachtungen von Beratungsgesprächen für Ausländer mit NFIBEF oder ausländischen Qualifikationen (N = 14) angestellt und Dokumentenanalyse (N = 49) angewendet. Die Studie konzentrierte sich insbesondere auf 14 Fallstudien bestehend aus sieben Flüchtlingen und sieben Regelungen zur Bewertung und Anerkennung von Fähigkeiten im Bundesland Baden-Württemberg." (Autorenreferat ; BIBB-Doku)
Keywords: P 1.5 Migranten; S 2.2.4.4 Anerkennung non-formaler Qualifikationen; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; I 2.1 Deutschland; I 2.1.2.4 Baden-Württemberg; Migration; Migrant; Bundesrepublik Deutschland; Berufsausbildung; Duales System; Anerkennung; Informelle Kompetenz; Nicht-formale Qualifikation; Arbeitsmarkt; Arbeitsmarktchance; Bourdieu, Pierre; Fallstudie; Baden-Württemberg